Insulin resistance, mTOR and hidradenitis suppurativa. (24th October 2018) - Marasca, C.; Balato, A.; Annunziata, M.C.; Cacciapuoti, S.; Fabbrocini, G.
Abstract : Linked article: This article is commented on by J.L. Hernández et al., p. e109 in this issue. To view this article visit https://doi.org/10.1111/jdv.15273